Pengaruh Gaya Kepemimpinan Demokrasi Terhadap Kinerja Aparat Desa - Karsum Bilaleya; Irina Popoi; Melizubaida Mahmud; Usaman Moonti; Agil Bahsoan (Journal of Economic and Business Education, 2023)
The results of the hypothesis testing carried out in this study, seen from the sig. of 0.000 0.05 indicates that there is an influence from the democratic leadership style on the performance of village officials, which means that the democratic leadership style influences performance in Pilobuhuta, Batudaa sub-district, Gorontalo district. Thus, the research hypothesis which states that there is an influence between the democratic leadership style on the performance of village officials in Pilobuhuta, Batudaa sub-district, Gorontalo district, is accepted in this study. Based on the results of testing the hypothesis in this study, it was found that democratic leadership style had a positive effect on the performance of Pilobuhuta Village officials, Batudaa District, Gorontalo Regency with a large correlation coefficient value as a sign of the closeness of the relationship, namely very strong and a large determination coefficient value as a sign of a large percentage level. the influence of the democratic leadership style variable on the performance of village officials is 52.5%.